In Vitro Cell-Based Biomarkers Study of Vital Organs: Impact of the Biofield Energy Based Test Formulation - Krista, Joanne Callas; Mahendra, Kumar Trivedi; Alice, Branton; Dahryn, Trivedi; Gopal, Nayak; Mayank, Gangwar; Snehasis, Jana (Journal of Human Health Research, 2019)
The present study was undertaken to evaluate the impact of Biofield Energy Treated test formulation using multiple cell-lines. The test formulation and cell media (Med) was divided into two parts; one part was untreated (UT) and other part received Biofield Energy Treatment remotely by a renowned Biofield Energy Healer, Krista Joanne Callas, USA and labeled as Biofield Energy Treated (BT) test item (TI)/Med. Based on cell viability, test formulation was found safe. Cytoprotective action of test formulation showed significant restoration of cell viability by 89.9% and 106.4% in human cardiac fibroblasts cells (HCF) cells, while improved restoration of cell viability by 77.3% and 69% in HepG2 cells compared to untreated. Cellular restoration in A549 cells was also improved by 141.2% and 157.1% compared to untreated. ALP activity was significantly increased by 118.7% and 140.7% in UT-Med + BT-TI and BT-Med + UT-TI, respectively at 0.1 µg/mL than untreated. Percent cellular protection of HCF (heart) cells (decreased of LDH activity) was significantly increased by 89.9% and 106.4% in UT-Med + BT-TI and BT-Med + BT-TI, respectively than untreated. HepG2 cells protection (decreased ALT activity) was increased by 59.8% in BT-Med + BT-TI than untreated. Superoxide dismutase (SOD) level was increased by 22.8% in BT-Med + BT-TI than untreated. Serotonin level was significantly increased by 361.7% and 197.6% in BT-Med + UT-TI and BT-Med + BT-TI, respectively than untreated in human neuroblastoma cells (SH-SY5Y). However, relative quantification (RQ) of vitamin D receptor (VDR) was significantly increased by 116.5%, 214.7%, and 241.5% in UT-Med + BT-TI, BT-Med + UT-TI, and BT-Med + BT-TI, respectively than untreated in MG-63 cells. Overall, data showed a significant improvement of organ-specific functional enzyme biomarkers. Thus, Biofield Energy Treated Test formulation (the Trivedi Effect®) would be useful for multiple organs health that can be beneficial against coronary artery disease, arrhythmias, congenital heart disease, cardiomyopathy, cirrhosis, liver cancer, hemochromatosis, asthma, chronic bronchitis, cystic fibrosis, osteoporosis, etc.
Keywords: The Trivedi Effect®; Biofield Energy Treatment; Organ health; Bone health; Functional biomarker